Ceritinib compassionate use for patients with crizotinib-refractory, anaplastic lymphoma kinase-positive advanced non-small-cell lung cancer. (February 2018) - Metro, Giulio; Passaro, Antonio; Lo Russo, Giuseppe; Bonanno, Laura; Giusti, Raffaele; Gregorc, Vanesa; Capelletto, Enrica; Martelli, Olga; Cecere, Fabiana L; Giannarelli, Diana; Luciani, Andrea; Bearz, Alessandra; et al.
Aim: Ceritinib was evaluated within a compassionate use program of Italian patients.Patients & methods: 70 patients with anaplastic lymphoma kinase-positive crizotinib-refractory advanced non-small-cell lung cancer received ceritinib.Results: Overall response was 40.6%, median progression-free survival was 8.2 months and median survival was 15.5 months. Dose reduction due to treatment-related adverse events occurred in 50.8% of patients starting at 750 mg/day. No significantly different progression-free survival was observed between patients who underwent any time dose reduction (n = 38) versus those who remained on the recommended dose of 750 mg/day (n = 32; p = 0.07).Conclusion: The efficacy of ceritinib compassionate use program resembled that of clinical trials. Dose reductions and adjustments did not appear to negatively affect clinical outcome.